Biochemical Response in Women to Certain Selected Exercises - Mangayarkarasi, S. (Asian Journal of Chemistry, 2010)
Rope skipping is an ideal indoor exercise that helps to improve a woman's appearance, by toning up the muscles in the body. This life-time fitness activity being performed by college women over a period of 10 weeks has improved the haemoglobin content in the blood. This biochemical change that has occurred in women is being presented.